2020
DOI: 10.1039/d0ay01194k
|View full text |Cite
|
Sign up to set email alerts
|

Nano-liquid chromatography-mass spectrometry and recent applications in omics investigations

Abstract: Liquid chromatography coupled to mass spectrometry (LC-MS) is one of the most powerful tools in identifying and quantitating molecular species. Decreasing column diameter from the millimeter to micrometer scale is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 145 publications
(148 reference statements)
0
23
0
Order By: Relevance
“…This fact was established during keyword mining as well as bioconcept co-occurrence networks. The frequent keywords also suggested that the most frequent methodologies are 2D-gel-electrophoresis, mass spectrometry, matrix-assisted laser desorption-ionization, liquid chromatography, computational biology which are the most common ones in the case of proteome and proteomics research [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This fact was established during keyword mining as well as bioconcept co-occurrence networks. The frequent keywords also suggested that the most frequent methodologies are 2D-gel-electrophoresis, mass spectrometry, matrix-assisted laser desorption-ionization, liquid chromatography, computational biology which are the most common ones in the case of proteome and proteomics research [ 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, back in 2008, EVs proteomic analysis in C. neoformans led to identification of 76 proteins ( Rodrigues et al, 2008 ). Current high-resolution tandem mass spectrometry (HR-MS/MS)-based approaches ( Lesur and Domon, 2015 ), including nanoflow liquid chromatography coupled to HR-MS/MS (nanoLC-HR-MS/MS; Sanders and Edwards, 2020 ), allow to identify and quantify over 2,000 proteins in fungal EVs ( Zhao et al, 2019 ; Cleare et al, 2020 ). In this section, we will cover recent technological advances and their current impact and perspectives in analyzing fungal EVs.…”
Section: New Methodologies and Instrumentationmentioning
confidence: 99%
“…A comprehensive summary of theory, common approaches, and over 20 of the most recent applications of nano-LC-MS in metabolomics and lipidomics investigation can be found elsewhere. 232 Single cell analysis is an emerging application of small-scale metabolomics by nano-LC-MS. Recently, Nakatani et al reported a method for derivatization-free targeted quantification of hydrophilic metabolites in single HeLa cells.…”
Section: Navigating the Conflicting Goals Of Metabolome Coverage And mentioning
confidence: 99%
“…In such cases, the full sensitivity potential of nano-RP-LC-MS platforms may be exploited by analyte derivatization, increasing RP-retention and ionization efficiency. A comprehensive summary of theory, common approaches, and over 20 of the most recent applications of nano-LC-MS in metabolomics and lipidomics investigation can be found elsewhere . Single cell analysis is an emerging application of small-scale metabolomics by nano-LC-MS.…”
Section: Navigating the Conflicting Goals Of Metabolome Coverage And ...mentioning
confidence: 99%